The bookstore diaries - Mallery, Susan (Mira, 2026)
Jax has a slight issue with control--as in, she needs it. Always. Too bad she has power only over the Painted Lady Bookstore, the Victorian mansion turned bookshop she inherited. No one else listens to a word she says. Her ex gets engaged for questionable reasons. Her beloved sister, Ryleigh, wants to move away to find a husband. And the handsome contractor Jax has chosen to convince Ryleigh to stay is only interested in Jax. Still, she's living the bookworm dream--until an unhappy accident erases the names from the bookshop lockboxes where the town keeps their diaries. Which means the only way to find a diary's owner is--to read it. As secrets spill and scandals surface, life at the Painted Lady Bookstore gets a lot more colorful and chaotic. But for a woman who's always had to take charge, Jax will see that losing control--especially with the right wrong guy--can set you free.